The Problems Faced by Physiotherapy Students and Their Causes in Completing Reading Comprehension Section of ITP TOEFL - Meladina, Meladina; Dasril, Dasril (Elsya : Journal of English Language Studies, 2021)
TOEFL is an important English test that should be taken by all university students from all the study programs in Indonesia. Each student needs to know all English skills tested and master those skills as well. This study was conducted to investigate the difficulties faced by non-English students, namely students of physiotherapy study program with section three reading comprehension of International Testing Program (ITP) TOEFL as well as the causes of difficulties encountered. The type of this research was descriptive quantitative. Using total sampling technique, all of 36 physiotherapy students in the University of Fort De Kock Bukittinggi were chosen as the samples. The data were collected through a multiple-choice test consisting of 50 questions with four options and questionnaire. The data were then analyzed using Roger’s 2011 theory on the seven types of questions of reading tested in ITP TOEFL. The results showed that all of the students had problems with main idea (24.0%), factual question (26.1%), inference question (26.3%), vocabularies in-context (29.4%), and negative question (34.4%) (difficult questions, scanning (13.8%) and reference question (18.0%) (the most difficult questions. These problems are caused by a number of factors such as feeling panic to face long passages, limitation of vocabularies, lack of practice, and less motivation. Therefore, English teachers and trainers are strongly encouraged to pay more attention to the reading problems faced by the students in ITP TOEFL as well as the causes of the problems by facilitating and providing more study exercises and practice.